Development of a novel fuse type mechanical connector. (October 2022) - Şenol, Erkan; Yüksel, Ercan; Özkaynak, Hasan; Soydan, Cihan; Sürmeli, Melih; Karakuş, Kubilay; Saruhan, Hakan
Abstract: A novel fuse-type mechanical connector (FTMC) is developed, as a robust connection tool for use in the moment-resisting beam to column connections in precast concrete construction. The connection decouples bending moment to axial force couples on FTMCs, as well as shear force is transferred by the steel hinge that connects the column shear plate to the beam web. The challenging features of FTMC are to be a robust mechanical connection, plastic deformation accumulation on the fuse element, and demount ability. The development studies of FTMC are presented in this paper. The experiments subjected to monotonic and cyclic loading exhibited that the final design of FTMC could dissipate a large amount of energy by yielding the fuse element. A robust numerical model was generated to estimate the cyclic behavior of FTMC and the performed test results validate it.